Analisis Tabel Input-Output pada Sektor Pariwisata Jawa Tengah Pasca Covid - Reikha Habibah Yusfi; Shanty Oktavilia; Nurjannah Rahayu Kistanti; Tutik Tutik; Retno Febriyastuti Widyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Covid-19 pandemic has caused many economic activities and workforce productivity to decline. The tourism sector is a dynamic sector because it can involve many people and revitalize various business fields. Considering the strategic position of the tourism sector, research is necessary to determine its impact on the economy post-Covid-19. The objectives of this study include analyzing key sectors against the 2016 Central Java IO Table to identify sectors with high backward and forward linkages as considerations for economic recovery after the Covid-19 pandemic. The 2016 Central Java IO Table and information on Central Java tourist expenditure were used to analyze the impact of tourism sector demand. The results of the sectoral backward linkage analysis show that only the Food and Beverage Service sector is included in the top 10. Meanwhile, the sectoral forward linkage analysis found that the Food and Beverage Service sector and the Information and Communication Services sector are included in the top 10. The analysis of the impact of final demand on all tourism sectors in Central Java in 2021 reached 16,663,997.66 million rupiah.